Answering the crisis with intellectual activism: Making a difference as business schools scholars. (May 2020) - Contu, Alessia
Should business school scholars engage in intellectual activism? This article explicates the origin, the intellectual tradition and politics of intellectual activism, making a case for why management scholars might want to become intellectual activists. Intellectual activism has been elaborated in Patricia Hill Collins' contributions and the work of other black feminist intellectuals and activists such as Angela Davis. Together with the writings of Antonio Gramsci and Judith Butler, intellectual activism is reframed here as a particular type of critical performativity to help scholars make a difference in the world. This article invites scholars to answer the challenges posed by the crisis of neoliberalism, and to re-articulate the values of equality, freedom and solidarity by embodying an academic praxis that is progressive, intersectional, critical and concretely engaged in the service of social, economic and epistemic justice. The article also provides examples of intellectual activism by showcasing the activities of the critical management association, Vida.